2021
DOI: 10.3389/fphys.2021.678407
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Restriction Training: To Adjust or Not Adjust the Cuff Pressure Over an Intervention Period?

Abstract: Blood flow restriction (BFR) training combines exercise and partial reduction of muscular blood flow using a pressured cuff. BFR training has been used to increase strength and muscle mass in healthy and clinical populations. A major methodological concern of BFR training is blood flow restriction pressure (BFRP) delivered during an exercise bout. Although some studies increase BFRP throughout a training intervention, it is unclear whether BFRP adjustments are pivotal to maintain an adequate BFR during a train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…Additionally, no adverse events related to BFR-W were observed. This may be explained by the relatively low occlusion pressure at 60%, which may minimise the risk of adverse events, as suggested by Cerqueira et al 31 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, no adverse events related to BFR-W were observed. This may be explained by the relatively low occlusion pressure at 60%, which may minimise the risk of adverse events, as suggested by Cerqueira et al 31 .…”
Section: Discussionmentioning
confidence: 89%
“…The cuff was inflated to 100 mmHg and then the pressure was gradually increased by 20 mmHg until the arterial pulse was no longer detectable with the Ultrasound Doppler, which was defined as LOP 30 . If the patients experienced pain and discomfort at 60% LOP, the pressure was decreased by 20 mmHg ( n =2) 31 .…”
Section: Methodsmentioning
confidence: 99%
“…In terms of cardiac morphology, function, and blood pressure, studies have shown that BFR exercise has a positive effect on the cardiac function and heart rate variability of healthy people, elderly people, and some patients with coronary artery disease, and improved the cardiac contractility and anti-ischemic ability, reduced heart rate and blood pressure, and increased heart rate variability ( 21 24 ). The same results were obtained in a study of elderly rats, in which BFR exercise improved cardiac function and arterial compliance ( 15 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pressure is also an important factor in BFR. The cuff width, limb circumference, ankle-brachial index, fat and muscle thickness, arterial stiffness, endothelial function, and blood pressure all influence the BFR pressure ( 116 ). The optimal limiting pressure value for BFRT should be high enough to allow venous blood flow to the occluded muscle but low enough to maintain arterial blood flow to the muscle.…”
Section: Variables That Influence the Effectiveness Of Bfrtmentioning
confidence: 99%